Coaly Petroleum Source Rocks in Malaysia - Is the Present the Key to the Past? - Kim-Kiat Liaw (Berita Sedimentologi, 2019)
Malaysia’s three oil-producing regions are: (1) Malay Basin, (2) Sarawak Basin, (3) Sabah Basin. Though, basin evolutions differ somewhat, the petroleum systems remain broadly similar. Other than Central Luconia, which is distinctively a carbonate gas province, the other provinces are characterised by accumulations of oil and gas found within Neogene clastic reservoirs. HC charge was derived principally from a Type III coaly source rock (SR) e.g., (i) in-situ pure coal and/or impure shaly coal, (ii) transported coaly clasts/fragments in channel lag deposits, (iii) finely-dispersed detritus, and also, commonly as coaly laminae/bands, mostly in marine deposits.